2012
DOI: 10.1179/1362171812y.0000000043
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic detection technology for tiny flaws in FSW of aluminium alloy

Abstract: The present paper put forward a magnetic non-destructive testing method for the complex tiny flaws existing in the friction stir welding (FSW) of aluminium alloy. Through magnetisation testing, it is confirmed that the relative magnetic permeability of aluminium alloy material is larger than the relative magnetic permeability of aluminium. Aluminium alloy is a paramagnetic material. The anomalous characteristics of the magnetic field in the flaw were analysed according to the differences of the relative magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Saliha Gachi et al 12 have reported that Xray radiography technique revealed the absence of weld defects at the surface and at inner zone of FSW weld joints of thick aluminium sheets. Yu et al 13 proposed a magnetic non-destructive technique to detect complex tiny flaws in the FSW of aluminium alloys. The anomalous characteristics of the magnetic field in the flaw are analyzed using a magnetic sensor with 1nT resolution in which the difference of the relative permeability of the flaws is detected in geomagnetic field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saliha Gachi et al 12 have reported that Xray radiography technique revealed the absence of weld defects at the surface and at inner zone of FSW weld joints of thick aluminium sheets. Yu et al 13 proposed a magnetic non-destructive technique to detect complex tiny flaws in the FSW of aluminium alloys. The anomalous characteristics of the magnetic field in the flaw are analyzed using a magnetic sensor with 1nT resolution in which the difference of the relative permeability of the flaws is detected in geomagnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al . 13 proposed a magnetic non-destructive technique to detect complex tiny flaws in the FSW of aluminium alloys. The anomalous characteristics of the magnetic field in the flaw are analyzed using a magnetic sensor with 1nT resolution in which the difference of the relative permeability of the flaws is detected in geomagnetic field.…”
Section: Introductionmentioning
confidence: 99%